Evaluation of structure and mechanical properties of Ni–P–Al2O3 nanocomposite coatings - Alirezaei, S.; Vaghefi, SM Monir; Ürgen, M.; Saatchi, A.; Kazmanli, K. (SAGE Publications, 2012)
In this article, alumina nanoparticles were co-deposited within Ni–P electroless coating on mild steel samples and then isothermal heat treatment was done at 400℃ for 1 h. The size distribution of nanoparticles was evaluated by transmission electron microscopy and the concentration of alumina reinforcements in Ni–P matrix was determined using field emission scanning electron microscopy and image analysis software. The phase transformation of coatings was analysed by X-ray diffraction and differential thermal analysis. Also, mechanical properties of coatings were evaluated by microhardness and indentation tests. The results showed that mechanical properties of Ni–P–Al2O3 nanocomposite coatings strongly influences by dispersion and/or precipitation hardening mechanisms.